INSTALASI PENERANGAN DARURAT DESA SUKAMULYA KABUPATEN CIANJUR - Sartono Sartono; Yogi Priyo Istiyono; Rahmat Saputra; Siti Fatimatul Zuhro; Suryo Sulistyo (LPPM Universitas Bina Bangsa, 2022)
Installing emergency lights is very useful when the electricity supply from PLN is interrupted. This also happened during the Cianjur Earthquake on November 21, 2022 at 13:21:10 WIB. The epicenter of the earthquake was at coordinates 6.84 LS – 107.05 and a depth of 11 km with a magnitude of 5.6. As of November 28, 2022, at 07:00 WIB, BMKG has recorded 297 aftershocks with the largest magnitude of M 4.2 and the smallest M 1.0, resulting in the collapse of houses, places of worship and other community facilities.. Miniature Circuit Breakers (MCB) 10A have been installed as main switch light to back up emergency residential lighting for 9 heads of family. In addition to lights, the team also installed 3-hole terminals for other electrical equipment such as magic com, television, iron and others. Based on visual observation, since the lights were installed in the room and terrace, they look more cheerful and happy and enthusiastic in activities such as cooking, washing, going to the mosque, chatting with family members and receiving guests. The traffic intensity of residents in the neighborhood is also smooth, especially at night